Early child development and maternal labor force participation: using handedness as an instrument - Paul Frijters; David W. Johnston; Manisha Shah; Michael A. Shields (Institute for the Study of Labor (IZA), 2008)
We estimate the effect of early child development on maternal labor force participation using data from teacher assessments. Mothers might react to having a poorly developing child by dropping out of the formal labor force in order to spend more time with their child, or they could potentially increase their labor supply to be able to provide the funds for better education and health resources. Which action dominates is therefore the empirical question we seek to answer in this paper. Importantly, we control for the potential endogeneity of child development by using an instrumental variables approach, uniquely exploiting exogenous variation in child development associated with child handedness. We find that having a poorly developing young child reduces the probability that a mother will participate in the labor market by about 25 percentage points.
urn:nbn:de:101:1-20080613104
Keywords: J22; 330; Child development; maternal labor force participation; handedness; Frauenerwerbstätigkeit; Mütter; Kinder; Persönlichkeitspsychologie; Schätzung; Australien